Effect of Free Cash Flow on Firm Value - Radi Abd Ali, Ahmed (University of Thi-Qar Journal, 2024)
This research aims to examine how free cash flow affects the value of a company. The investors’ assessment of the level of success of a company is known as the value of the company. Many previous studies have indicated that free cash flow is among the variables that affect the value of a company. According to some studies, the value of a company increases with the amount of free cash flow generated by the company. While the other study produced a different result, the value of the company decreased with the increase in the free cash flow owned by the company. Therefore, the result regarding the effect of the impact of free cash flow remains unclear. In order to achieve the research objectives, the researcher presented a measurement of the company’s value using free cash flow equations based on the Capital Asset Pricing Model (CAPM), through the parameters of the equation represented by measuring the market portfolio return and the stock return, and the risk beta, which is the basic parameter of the equation and reaching the required rate, to obtain the weighted average cost of capital (WACC) rate, which is the basic in measuring the company’s value. The researcher also reached the preparation of a free cash flow statement and measuring the final value using the perpetual growth approach, which is based on the Gordon growth model. The researcher reached a set of conclusions, the most important of which are: Measuring the company’s value using free cash flow provides accuracy and suitability in achieving results and showing the real value of the company in which the investor wishes to invest by purchasing its shares, and that using the free cash flow model in measuring the company’s value is one of the best means of measurement because it achieves more appropriate and more accurate results.